A Comparison of the Mental Health Legislations in the Australian Capital Territory (ACT) and England and Wales (E&W) and the Resulting Impacts on Involuntary Hospitalisation Rates, Average Detention Lengths and Tribunal Reviews - Anju Soni; Ian Treasaden (BJPsych Open)
Aims: With reform planned for the England and Wales (E&W) Mental Health Act (MHA)1983 as amended by the MHA 2007, a comparison of the current E&W Act with the Australian Capital Territory (ACT) MHA 2015 was undertaken, including to examine whether differences were associated with variations in involuntary hospitalisation and Tribunal reviews.